Determination of signal calcineurin pathway biomarkers significance in early myocardial changes in children with bicuspid aortic valve - Kamenshchyk, Andrey (ScienceRise: Medical Science, 2017)
Aim of research: determination of the diagnostic value of serum concentration of biomarkers of calcineurin signal pathway (calcineurin, protein S100, interleukin-2) in children with the bicuspid aortic valve at absence of heart failure signs and influence of revealed changes on the early remodeling and hypertrophy of myocardium. Materials and methods: 38 children with the bicuspid aortic valve (SAV), diagnosed by doppleroechocardiography, and 28 children of the control group underwent the measuring of concentrations of calcineurin, protein S100, interleukin-2 and general calcium by the immune-enzyme method with the further estimation of the influence of these changes on morphofunctional hearth parameters by the method of correlation analysis. Results: children with SAV demonstrated the reliable thickening of the back wall of the left ventricle and interventricular septum at the correspondent increase of the blood velocity and pressure gradient on the aortic valve. Serum concentrations of calcineurin and calcium in children with SAV were reliably decreased, and protein S100 correspondingly increased comparing with the control group. At that the SAV group, as opposite to the control one, demonstrated reliable negative correlations between the calcineurin level and right ventricle sizes, protein S100 and left and right atria sizes interleukin-2 and left ventricle systolic size at the reliable positive correlation between levels of calcineurin and general calcium. Conclusions: Children with SAV demonstrated the moderately expressed left ventricle myocardium hypertrophy, decrease of calcineurin serum concentrations that have a negative influence on the geometry of right heart parts and serum calcium level at the correspondent increase of protein S100. The revealed changes allowed to establish the predicative role of calcineurin in the development of early morphofunctional changes of myocardium in children with SAV